Usefulness of Pelvic Radiographs in the Initial Trauma Evaluation with Concurrent CT: Is Additional Radiation Exposure Necessary? - Anne K. Misiura; Autumn D. Nanassy; Jacqueline Urbine (International Journal of Pediatrics)
Trauma patients in a Level I Pediatric Trauma Center may undergo CT of the abdomen and pelvis with concurrent radiograph during initial evaluation in an attempt to diagnose injury. To determine if plain digital radiograph of the pelvis adds additional information in the initial trauma evaluation when CT of the abdomen and pelvis is also performed, trauma patients who presented to an urban Level I Pediatric Trauma Center between 1 January 2010 and 7 February 2017 in whom pelvic radiograph and CT of the abdomen and pelvis were performed within 24 hours of each other were analyzed. A total of 172 trauma patients had pelvic radiograph and CT exams performed within 24 hours of each other. There were 12 cases in which the radiograph missed pelvic fractures seen on CT and 2 cases in which the radiograph suspected a fracture that was not present on subsequent CT. Furthermore, fractures in the pelvis were missed on pelvic radiographs in 12 of 35 cases identified on CT. Sensitivity of pelvic radiograph in detecting fractures seen on CT was 65.7% with a 95% confidence interval of 47.79-80.87%. Results suggest that there is no added diagnostic information gained from a pelvic radiograph when concurrent CT is also obtained, a practice which exposes the pediatric trauma patient to unnecessary radiation.